2017
DOI: 10.1017/s1041610216002155
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of Kundalini yoga in mild cognitive impairment

Abstract: Background:Global population aging will result in increasing rates of cognitive decline and dementia. Thus, effective, low-cost, and low side-effect interventions for the treatment and prevention of cognitive decline are urgently needed. Our study is the first to investigate the effects of Kundalini yoga (KY) training on mild cognitive impairment (MCI).Methods:Older participants (≥55 years of age) with MCI were randomized to either a 12-week KY intervention or memory enhancement training (MET; gold-standard, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
137
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(145 citation statements)
references
References 46 publications
7
137
0
1
Order By: Relevance
“…A total of 32 randomized clinical trials with 3624 participants were included in the analysis. The age of the included participants ranged from 50 to 85 years.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 32 randomized clinical trials with 3624 participants were included in the analysis. The age of the included participants ranged from 50 to 85 years.…”
Section: Resultsmentioning
confidence: 99%
“…Because mind‐body exercise is a nonpharmacologic therapy, nearly all of the studies failed to blind the participants and personnel. The outcome assessments were blinded in 20 studies (62.5%) . Thirty studies (93.75%) had a low risk of attrition bias because most studies reported the dropout rate or represented detailed explanations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations